Pidana Kerja Sosial dalam KUHP Nasional dan Komparasinya dengan Wetboek van Strafrecht (WVSR) Belanda - Lindsay Dafy; Anita Zulfiani (Indonesian Journal of Social Sciences and Humanities, 2026)
Indonesia's retributive sentencing system, dominated by imprisonment, has caused serious problems including prison overcrowding. The Indonesian National Penal Code addresses this by incorporating community service as a principal punishment, marking a paradigm shift toward a rehabilitative approach. This study aims to compare the regulation of community service punishment in Indonesia's National Penal Code with the Dutch Wetboek van Strafrecht (WvSr) using normative legal research methods with statutory, conceptual, and comparative approaches. The findings reveal similarities in both systems regarding the classification of community service as one of primary sanction with its unpaid nature and the 240-hour maximum. However, significant differences exist when both penal code were being compared. The Indonesian National Penal Code restricts its application through sentencing thresholds and cumulative subjective criteria, whereas the WvSr offers a more flexible framework through categorical prohibitions for serious offenses, pre-adjudication mechanisms, sentence combinations, recidivism regulations, and a comprehensive juvenile justice sub-system.